Monitoring Pengetahuan Tanya 5O dan Dagusibu Obat yang Benar pada Ibu PKK RT/RW 003/003 Desa Kedanyang, Kebomas, Gresik - Janatun Na’imah; Anindi Lupita Nasyanka; Riskha Aulia (President University, 2020)
At this time, community does not understand classes of drugs that can be purchase or stored at home. This can have two impacts, positive and negative. The positive impact is community become more responsive to health, while the negative impact is increasing use of drugs which raises problems related to how to get, use, store and dispose of drugs properly or commonly known as Dagusibu. This community service activity aims to educating housewives as